An automatic facial landmarking for children with rare diseases. Issue 5 (30th January 2023) - Hennocq, Quentin; Bongibault, Thomas; Bizière, Matthieu; Delassus, Ombline; Douillet, Maxime; Cormier‐Daire, Valérie; Amiel, Jeanne; Lyonnet, Stanislas; Marlin, Sandrine; Rio, Marlène; Picard, Arnaud; Khonsari, Roman Hossein; et al.
Abstract: Two to three thousand syndromes modify facial features: their screening requires the eye of an expert in dysmorphology. A widely used tool in shape characterization is geometric morphometrics based on landmarks, which are precise and reproducible anatomical points. Landmark positioning is user dependent and time consuming. Many automatic landmarking tools are currently available but do not work for children, because they have mainly been trained using photographic databases of healthy adults. Here, we developed a method for building an automatic landmarking pipeline for frontal and lateral facial photographs as well as photographs of external ears. We evaluated the algorithm on patients diagnosed with Treacher Collins (TC) syndrome as it is the most frequent mandibulofacial dysostosis in humans and is clinically recognizable although highly variable in severity. We extracted photographs from the photographic database of the maxillofacial surgery and plastic surgery department of Hôpital Necker–Enfants Malades in Paris, France with the diagnosis of TC syndrome. The control group was built from children admitted for craniofacial trauma or skin lesions. After testing two methods of object detection by bounding boxes, a Haar Cascade‐based tool and a Faster Region‐based Convolutional Neural Network (Faster R‐CNN)‐based tool, we evaluated three different automatic annotation algorithms: the patch‐based active appearance model (AAM), the holistic AAM, and the constrained local model (CLM). The final error corresponding to the distance between the points placed by automatic annotation and those placed by manual annotation was reported. We included, respectively, 1664, 2044, and 1375 manually annotated frontal, profile, and ear photographs. Object recognition was optimized with the Faster R‐CNN‐based detector. The best annotation model was the patch‐based AAM ( p < 0.001 for frontal faces, p = 0.082 for profile faces and p < 0.001 for ears). This automatic annotation model resulted in the same classification performance as manually annotated data. Pretraining on public photographs did not improve the performance of the model. We defined a pipeline to create automatic annotation models adapted to faces with congenital anomalies, an essential prerequisite for research in dysmorphology.